DETERMINANTS OF BEHAVIOURAL INTENTION TOWARDS GREEN INVESTMENTS: THE PERSPECTIVES OF MUSLIMS (International Journal of Islamic Business, 2019)
Green investment in Malaysia is still in its infancy stage, due to lack of exposure of the green concept among the general population. It is a type of investment that considers the environmental aspects within the context of rigorous financial analysis. Accordingly, this study attempts to identify factors influencing Muslims’ intention to adopt green investment. The theory of planned behaviour (TPB) framework was adopted which include attitude, subjective norms, perceived behavioural control, knowledge, reputation and religious values. The data for the study were collected through self-administered questionnaires using a six point Likert Scale among 270 respondents in the Klang Valley area. This study discovered that the five variables comprising attitude, perceived behavioural control, knowledge, reputation and religious values significantly influenced Muslims’ intention to participate in green investment, with religious values as the most significant contributor. Correspondingly, some implications have been identified and future research directions are also indicated for promoting green investment.